The prenatal foundations of kin recognition - Yorick Lambreghts; Martin J. Whiting; Tobias Uller; Camilla M. Whittington; Geoffrey M. While (Trends in Ecology & Evolution, 2026)

Tiliquin lizards as a model vertebrate system for understanding the emergence of societies - Martin J. Whiting; Geoffrey M. While (Animal Behaviour, 2026)

A global analysis of field body temperatures of active squamates in relation to climate and behaviour - Shahar Dubiner; Rocío Aguilar; Rodolfo O. Anderson; Diego M. Arenas Moreno; Luciano J. Avila; Estefania Boada‐Viteri; Martin Castillo; David G. Chapple; Christian O. Chukwuka; Alison Cree; Félix B. Cruz; Guarino R. Colli; et al. (Global Ecology and Biogeography, 2024)
Aim Squamate fitness is affected by body temperature, which in turn is influenced by environmental temperatures and, in many species, by exposure to solar radiation. The biophysical drivers of body temperature have been widely studied, but we lack an integrative synthesis of actual body temperatures experienced in the field, and their relationships to environmental temperatures, across phylogeny, behaviour and climate. Location Global (25 countries on six continents). Taxa Squamates (210 species, representing 25 families). Methods We measured the body temperatures of 20,231 individuals of squamates in the field while they were active. We examined how body temperatures vary with substrate and air temperatures across taxa, climates and behaviours (basking and diel activity). Results Heliothermic lizards had the highest body temperatures. Their body temperatures were the most weakly correlated with substrate and air temperatures. Body temperatures of non‐heliothermic diurnal lizards were similar to heliotherms in relation to air temperature, but similar to nocturnal species in relation to substrate temperatures. The correlation of body temperature with air and substrate temperatures was stronger in diurnal snakes and non‐heliothermic lizards than in heliotherms. Body‐substrate and body‐air temperature correlations varied with mean annual temperatures in all diurnal squamates, especially in heliotherms. Thermal relations vary with behaviour (heliothermy, nocturnality) in cold climates but converge towards the same relation in warm climates. Non‐heliotherms and nocturnal species body temperatures are better explained by substrate temperature than by air temperature. Body temperature distributions become left‐skewed in warmer‐bodied species, especially in colder climates. Main Conclusions Squamate body temperatures, their frequency distributions and their relation to environmental temperature, are globally influenced by behavioural and climatic factors. For all temperatures and climates, heliothermic species' body temperatures are consistently higher and more stable than in other species, but in regions with warmer climate these differences become less pronounced. A comparable variation was found in non‐heliotherms, but in not nocturnal species whose body temperatures were similar to air and substrate irrespective of the macroclimatic context.

Competitive asymmetries, birthing asynchrony and sibling rivalry in a social lizard - Alix Bouffet-Halle; Erik Wapstra; Geoffrey M. While (Behavioral Ecology and Sociobiology, 2024)
Family life often involves interactions between individuals who have different fitness goals, leading to conflict. Resolution of this conflict is key for the stabilisation of family life. Here, we used a lizard, Liopholis whitii , that lives in facultative family groups to characterise the nature and extent of sibling conflict and test the role that individual and litter characteristics play in shaping conflict between family members. We found significant variation in conflict between family groups, specifically in relation to siblings. In approximately half of the litters, siblings were aggressive towards one another, while in the other half of litters, there was no aggression observed between siblings. There were no differences between aggressive and non-aggressive litters in the key factors predicted to mediate conflict, including sex, offspring size, or litter size. However, in aggressive litters, the maximum amount of within-litter conflict decreased with an increase in the spread between births of siblings. First-born offspring were significantly more likely to be aggressive towards their siblings compared to second and third born offspring. While one offspring was usually the target of that aggression, we found no evidence that any individual-level factor predicted who received aggression. In aggressive litters, aggressive offspring spent a greater amount of time with their mother compared to non-aggressive offspring. Similar asymmetries in the amount of time offspring spent with their mother between siblings were also observed in non-aggressive litters. Combined, our results suggest that birth order is the main driver of sibling conflict in aggressive litters in this facultatively social lizard species, suggesting that birthing asynchrony may provide females with a mechanism to manage conflict. Significance statement Conflict is a ubiquitous aspect of family life; it occurs between adults, between parents and offspring as well as between siblings. We show that the extent of conflict between siblings varies considerably within and between families in a lizard that exhibits prolonged associations between parents and offspring. We found no effects of offspring sex or size on within or between litter conflict. Instead, the number of days that passed between the birth of offspring appears to be the main factor that influences how much conflict there is between siblings. Furthermore, birth order was the main factor predicting which offspring was dominant. Combined this suggests that birthing asynchrony, the ability of females to spread out births across multiple days, may play a crucial role in the management of conflict in this system. As the moderation of conflict is crucial for the stabilisation of family life, these results provide important insights into the early evolution of social life.

Genetic structure, diversity and distribution of a threatened lizard affected by widespread habitat fragmentation - Anna F. Senior; Nick Clemann; Michael G. Gardner; Katherine A. Harrisson; Geoffrey M. While; David G. Chapple (Conservation Genetics, 2022)

Degrees of change: between and within population variation in thermal reaction norms of phenology in a viviparous lizard - George D. Cunningham; Geoffrey M. While; Mats Olsson; Gabriella Ljungström; Erik Wapstra (Ecology, 2020)
As the earth warms, populations will be faced with novel environments to which they may not be adapted. In the short term, populations can be buffered against the negative effects, or maximize the beneficial effects, of such environmental change via phenotypic plasticity and, in the longer term, via adaptive evolution. However, the extent and direction of these population‐level responses will be dependent on the degree to which responses vary among the individuals within them (i.e., within population variation in plasticity), which is, itself, likely to vary among populations. Despite this, we have estimates of among‐individual variation in plastic responses across multiple populations for only a few systems. This lack of data limits our ability to predict the consequences of environmental change for population and species persistence accurately. Here, we utilized a 16‐yr data set from climatically distinct populations of the viviparous skink Niveoscincus ocellatus tracking over 1,200 litters from more than 600 females from each population to examine inter‐ and intrapopulation variability in the response of parturition date to environmental temperature. We found that these populations share a common population‐mean reaction norm but differ in the degree to which reaction norms vary among individuals. These results suggest that even where populations share a common mean‐level response, we cannot assume that they will be affected similarly by altered environmental conditions. If we are to assess how changing climates will impact species and populations accurately, we require estimates of how plastic responses vary both among and within populations.

Low food availability during gestation enhances offspring post-natal growth, but reduces survival, in a viviparous lizard - Thomas Botterill-James; Kirke L. Munch; Ben Halliwell; David G. Chapple; Michael G. Gardner; Erik Wapstra; Geoffrey M. While (Oecologia, 2019)

The diversity of population responses to environmental change - Fernando Colchero; Owen R. Jones; Dalia A. Conde; David Hodgson; Felix Zajitschek; Benedikt R. Schmidt; Aurelio F. Malo; Susan C. Alberts; Peter H. Becker; Sandra Bouwhuis; Anne M. Bronikowski; Kristel M. De Vleeschouwer; et al. (Ecology Letters, 2019)
The current extinction and climate change crises pressure us to predict population dynamics with ever‐greater accuracy. Although predictions rest on the well‐advanced theory of age‐structured populations, two key issues remain poorly explored. Specifically, how the age‐dependency in demographic rates and the year‐to‐year interactions between survival and fecundity affect stochastic population growth rates. We use inference, simulations and mathematical derivations to explore how environmental perturbations determine population growth rates for populations with different age‐specific demographic rates and when ages are reduced to stages. We find that stage‐ vs. age‐based models can produce markedly divergent stochastic population growth rates. The differences are most pronounced when there are survival‐fecundity‐trade‐offs, which reduce the variance in the population growth rate. Finally, the expected value and variance of the stochastic growth rates of populations with different age‐specific demographic rates can diverge to the extent that, while some populations may thrive, others will inevitably go extinct.

Genomic evidence for asymmetric introgression by sexual selection in the common wall lizard - Weizhao Yang; Geoffrey M. While; Hanna Laakkonen; Roberto Sacchi; Marco A. L. Zuffi; Stefano Scali; Daniele Salvi; Tobias Uller (Molecular Ecology, 2018)
Strongly selected characters can be transferred from one lineage to another with limited genetic exchange, resulting in asymmetric introgression and a mosaic genome in the receiving population. However, systems are rarely sufficiently well studied to link the pattern of introgression to its underlying process. Male common wall lizards in western Italy exhibit exaggeration of a suite of sexually selected characters that make them outcompete males from a distantly related lineage that lack these characters. This results in asymmetric hybridization and adaptive introgression of the suite of characters following secondary contact. We developed genomewide markers to infer the demographic history of gene flow between different genetic lineages, identify the spread of the sexually selected syndrome, and test the prediction that introgression should be asymmetric and heterogeneous across the genome. Our results show that secondary contact was accompanied by gene flow in both directions across most of the genome, but with approximately 3% of the genome showing highly asymmetric introgression in the predicted direction. Demographic simulations reveal that this asymmetric gene flow is more recent than the initial secondary contact, and the data suggest that the exaggerated male sexual characters originated within the Italian lineage and subsequently spread throughout this lineage before eventually reaching the contact zone. These results demonstrate that sexual selection can cause a suite of characters to spread throughout both closely and distantly related lineages with limited gene flow across the genome at large.

Mate familiarity and social learning in a monogamous lizard - Kirke L. Munch; Daniel W. A. Noble; Erik Wapstra; Geoffrey M. While (Oecologia, 2018)

Experimental manipulation suggests effect of polyandry but not mate familiarity on within-pair aggression in the social skink, Liopholis whitii - Thomas Botterill-James; Jacinta Sillince; Tobias Uller; David G. Chapple; Michael G. Gardner; Erik Wapstra; Geoffrey M. While (Behavioral Ecology and Sociobiology, 2017)

An experimental test of relatedness-based mate discrimination in a social lizard - Genevieve Bordogna; George Cunningham; Luisa J. Fitzpatrick; Ben Halliwell; Hannah E. A. MacGregor; Kirke L. Munch; Erik Wapstra; Geoffrey M. While (Behavioral Ecology and Sociobiology, 2016)

Loss of genetic diversity and increased embryonic mortality in non‐native lizard populations - Sozos N. Michaelides; Geoffrey M. While; Natalia Zajac; Fabien Aubret; Brittny Calsbeek; Roberto Sacchi; Marco A. L. Zuffi; Tobias Uller (Molecular Ecology, 2016)
Many populations are small and isolated with limited genetic variation and high risk of mating with close relatives. Inbreeding depression is suspected to contribute to extinction of wild populations, but the historical and demographic factors that contribute to reduced population viability are often difficult to tease apart. Replicated introduction events in non‐native species can offer insights into this problem because they allow us to study how genetic variation and inbreeding depression are affected by demographic events (e.g. bottlenecks), genetic admixture and the extent and duration of isolation. Using detailed knowledge about the introduction history of 21 non‐native populations of the wall lizard Podarcis muralis in England, we show greater loss of genetic diversity (estimated from microsatellite loci) in older populations and in populations from native regions of high diversity. Loss of genetic diversity was accompanied by higher embryonic mortality in non‐native populations, suggesting that introduced populations are sufficiently inbred to jeopardize long‐term viability. However, there was no statistical correlation between population‐level genetic diversity and average embryonic mortality. Similarly, at the individual level, there was no correlation between female heterozygosity and clutch size, infertility or hatching success, or between embryo heterozygosity and mortality. We discuss these results in the context of human‐mediated introductions and how the history of introductions can play a fundamental role in influencing individual and population fitness in non‐native species.

Sexual selection drives asymmetric introgression in wall lizards - Geoffrey M. While; Sozos Michaelides; Robert J. P. Heathcote; Hannah E. A. MacGregor; Natalia Zajac; Joscha Beninde; Pau Carazo; Guillem Pérez i de Lanuza; Roberto Sacchi; Marco A.L. Zuffi; Terézia Horváthová; Belén Fresnillo; et al. (Ecology Letters, 2015)
Hybridisation is increasingly recognised as an important cause of diversification and adaptation. Here, we show how divergence in male secondary sexual characters between two lineages of the common wall lizard ( Podarcis muralis ) gives rise to strong asymmetries in male competitive ability and mating success, resulting in asymmetric hybridisation upon secondary contact. Combined with no negative effects of hybridisation on survival or reproductive characters in F1‐hybrids, these results suggest that introgression should be asymmetric, resulting in the displacement of sexual characters of the sub‐dominant lineage. This prediction was confirmed in two types of secondary contact, across a natural contact zone and in two introduced populations. Our study illustrates how divergence in sexually selected traits via male competition can determine the direction and extent of introgression, contributing to geographic patterns of genetic and phenotypic diversity.

Widespread primary, but geographically restricted secondary, human introductions of wall lizards, Podarcis muralis - Sozos N. Michaelides; Geoffrey M. While; Natalia Zajac; Tobias Uller (Molecular Ecology, 2015)
Establishing the introduction pathways of alien species is a fundamental task in invasion biology. The common wall lizard, Podarcis muralis, has been widely introduced outside of its native range in both Europe and North America, primarily through escaped pets or deliberate release of animals from captive or wild populations. Here, we use Bayesian clustering, approximate Bayesian computation ( ABC ) methods and network analyses to reconstruct the origin and colonization history of 23 non‐native populations of wall lizards in England. Our analyses show that established populations in southern England originate from at least nine separate sources of animals from native populations in France and Italy. Secondary introductions from previously established non‐native populations were supported for eleven (47%) populations. In contrast to the primary introductions, secondary introductions were highly restricted geographically and appear to have occurred within a limited time frame rather than being increasingly common. Together, these data suggest that extant wall lizard populations in England are the result of isolated accidental and deliberate releases of imported animals since the 1970s, with only local translocation of animals from established non‐native populations. Given that populations introduced as recently as 25 years ago show evidence of having adapted to cool climate, discouraging further translocations may be important to prevent more extensive establishment on the south coast of England.

The scent of sun worship: basking experience alters scent mark composition in male lizards - Robert J. P. Heathcote; Emily Bell; Patrizia d’Ettorre; Geoffrey M. While; Tobias Uller (Behavioral Ecology and Sociobiology, 2014)

Promiscuity resolves constraints on social mate choice imposed by population viscosity - Geoffrey M. While; Tobias Uller; Genevieve Bordogna; Erik Wapstra (Molecular Ecology, 2014)
Population viscosity can have major consequences for adaptive evolution, in particular for phenotypes involved in social interactions. For example, population viscosity increases the probability of mating with close kin, resulting in selection for mechanisms that circumvent the potential negative consequences of inbreeding. Female promiscuity is often suggested to be one such mechanism. However, whether avoidance of genetically similar partners is a major selective force shaping patterns of promiscuity remains poorly supported by empirical data. Here, we show (i) that fine‐scale genetic structure constrains social mate choice in a pair‐bonding lizard, resulting in individuals pairing with genetically similar individuals, (ii) that these constraints are circumvented by multiple mating with less related individuals and (iii) that this results in increased heterozygosity of offspring. Despite this, we did not detect any significant effects of heterozygosity on offspring or adult fitness or a strong relationship between pair relatedness and female multiple mating. We discuss these results within the context of incorporating the genetic context dependence of mating strategies into a holistic understanding of mating system evolution.

Human introductions create opportunities for intra-specific hybridization in an alien lizard - Sozos Michaelides; Geoffrey M. While; Celia Bell; Tobias Uller (Biological Invasions, 2013)

The role of size and aggression in intrasexual male competition in a social lizard species, Egernia whitii - Jo McEvoy; Geoffrey M. While; David L. Sinn; Erik Wapstra (Behavioral Ecology and Sociobiology, 2013)